The effect of fermentation process on bioactive properties of some vegetables - Ozkan, K.; Sagdic, O. (PLAPIQUI(UNS-CONICET), 2025)
This study aimed at the effect of the fermentation process on bioactive compounds, physicochemical, microbial, and sensory properties changes in vegetables such as white cabbage (Brassica oleracea var. capitata f. alba), cucumber (Cucumis sativus L.), green beans (Phaseolus vulgaris L.). In this study, brine with 6 % salt content, sugar, and vinegar was added to vegetables in different formulations. While the antioxidant capacity of fresh cucumber, bean, and white cabbage samples was found as 33, 31, and 33 mu mol Trolox equivalent (TE)/g dry weight (DW), these values for fermented (pickled)vegetables were found as 57-100, 48-92, and 94-181 mu mol TE/g DW, respectively. Lactic acid bacteria (LAB) count in cucumber, bean, and white cabbage during lactic fermentation was found as 5.02-6.71, 4.17-6.66, and 5.12-7.28 log CFU/g, respectively. This study showed that the bioactive of the samples was increased during the fermentation process. The LAB changed the amounts of bioactive in the samples during fermentation. Therefore, a high correlation was found as a result of the correlation analysis between the LAB count and total phenolics, flavonoids, and antioxidant capacity.
Keywords: Pickle; Phenolic contents; Antioxidant capacity; Lactic acid bacteria; ANTIOXIDANT ACTIVITY; MULBERRY; Engineering